2020
DOI: 10.1016/j.jasrep.2020.102437
|View full text |Cite
|
Sign up to set email alerts
|

Archaeometrical results related to Neolithic amphibolite stone implements from Northeast Hungary

Abstract: 28 amphibolite Neolithic polished stone implements deriving from different archaeological localities and cultures in Northeast Hungary (Borsod-Abaúj-Zemplén County) were archaeometrically analysed by mainly non-destructive methods (MS, EDS/SEM, PGAA). Bulk chemistry of the samples showing subalkali characteristics. The amphibolite polished stone tools were divided into two groups based on their mineral components and metamorphic evolution. A single Ca-amphibole approach was used to calculate peak P-T condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…From Szerencs-Taktaföldvár the previously studied polished implements were amphibolite, contact metabasite, volcanites, sandstone and white stone (kaolin). The provenance of the amphibolite was Klátov, Gemericum (Slovakia) (Kereskényi et al 2020) while the contact metabasite derived from the Czech Massif (Kereskényi 2021). Detailed mineralogical analysis were not performed on the other lithotypes, therefore provenance cannot be established.…”
Section: Discussion -Possible Provenancementioning
confidence: 99%
See 1 more Smart Citation
“…From Szerencs-Taktaföldvár the previously studied polished implements were amphibolite, contact metabasite, volcanites, sandstone and white stone (kaolin). The provenance of the amphibolite was Klátov, Gemericum (Slovakia) (Kereskényi et al 2020) while the contact metabasite derived from the Czech Massif (Kereskényi 2021). Detailed mineralogical analysis were not performed on the other lithotypes, therefore provenance cannot be established.…”
Section: Discussion -Possible Provenancementioning
confidence: 99%
“…152 cm far from these findings, in a broken vessel, 12 polished stone implements were excavated (Hellebrandt 1979). Previous archaeometric studies were performed on 11 tools; five of them were identified as metabasite (Kereskényi et al 2020, Kereskényi 2021, and there were five more volcanites, one sandstone and one white stone (kaolin?) rock-typed adzes.…”
Section: Archaeological Background Previous Researchmentioning
confidence: 99%
“…The applied original surface method of SEM-EDS, XRD and PGAA are not sufficient enough to provide relevant results to determine precise provenance of greenstones. In a previous paper, thermobarometry was additionally applied to constrict the provenance of the greenstone implements which resulted to determination of different parts of the Western Carpathians (Kereskényi et al 2020, Kereskényi 2021). In the case of 1984.9.1. polished stone tool, significant magnetite content was observed, therefore the Little Carpathians (Ivan et al 2001) or the Slovak Ore Mountains (Faryad & Peterec 1987) might be concerned as a source area, meaning a nearby provenance field.…”
Section: Discussionmentioning
confidence: 99%
“…Amphibolite and greenschist is a very common raw material of polished stone tools in the northern part of Carpathian basin in the Neolithic era , Přichystal 2013, Kereskényi et al 2020). In addition, many geological amphibolite and greenschist outcrops expose in large amounts in the Western Carpathians (e.g.…”
Section: Possible Provenance Of Amphibolite-greenschist Implementsmentioning
confidence: 99%
See 1 more Smart Citation